Synopsis of Miridae (Hemiptera: Heteroptera) in Atlantic Forest Dominion, Espírito Santo State, Brazil: keys, diagnoses, new species, plant associations, and geographic distribution. Part I: Bryocorinae, Cylapinae and Deraeocorinae. - Ferreira, Paulo Sérgio Fiuza; Martins, David Dos Santos; Ferreira, Luciano Santana Fiuza; Fornazier, Maurício José (Zootaxa, 2024)
This is the first paper in a compilation of subfamilies synoptic taxonomic treatments of the Miridae in Espírito Santo (ES), Brazil based on extensive fieldwork and review of local collections. Starting with Bryocorinae, Cylapinae, and Deraeocorinae. This manuscript recognizes three subfamilies, 8 tribes, 31 genera, and 45 species from the region. Diagnoses, hostplant/plant associations and predator prey information, distribution data, and remarks are provided. Illustrations of adults and, for most species, morphological characters of male genitalia are given to help identification. Keys are included for identification, including other subfamilies, tribes, and genera not yet found in the state of ES to increase the comparative accuracy.